Self-Efficacy, Principals' Support, Stages Of Concern In Integrating E-Learning In The Jordanian Discovery Schools - Al-Rawajfih, Khader Khaleel (2010)

(untitled)
This study examines the effect of self-efficacy, perceptions of principals’ support and stages of concerns of teachers in Jordan Discovery schools on the integration of elearning into their teaching. The moderator variables identified were gender and teaching experiences. A total of 350 teachers were randomly stratified from all secondary Discovery schools in the four districts (strata) of the capital, Amman. The Concerns Based Approach Model and Rogers’ Diffusion of Innovation theory were used in this study. Data was gathered quantitatively by the use of 4 self-reporting instruments to measure (1) teachers’ self-efficacy, (2) perception of principals’ support, (3) teachers’ stages of concern and (4) teachers’ efforts to integrate e-learning into the teaching and learning process.